Evaluation of the Negative List for Investment in Historical Temple Objects: A Double-Edged Sword - Herman, Ronaldo Heinrich (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research will recommend the government regulate the service sector of operating historical and archaeological tourism as a closed business sector. Law No. 25 of 2007 and the Presidential Regulation No. 44 of 2016 has classified this matter as a business sector that is closed to investment. But Law No. 11 of 2020 and Presidential Regulation No. 10 of 2021 provide an opportunity for investors to invest in the field of service operations for historical and archaeological tourism. These laws open job opportunities and provide foreign exchange for the state from tourism at historical sites such as temples. However, the increase in investment also attracts more visitors, which could potentially harm the preservation of the Temple. This research will evaluate both Law No. 11 of 2020 and Presidential Regulation No. 10 of 2021. The evaluation will suggest how Presidential Regulation No. 49 of 2021 should regulate the classification of the field of services for the operation of historical and archaeological heritage tourism. The business sector should be classified as a closed business sector to fulfil the rights of future generations to historical knowledge.